ASPEK EKSTRAMUSIKAL PADA PADUAN SUARA VOCALISTA ANGELS KLATEN - Abraham Anton Febrindo Luwiga (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2022)
In the choir, two essential aspects, namely intramusical and extramusical aspects, playimportant roles in developing someone’s ability of singing and doing his or her dancemovements. Intramusical aspects are attached with a person’s ability in producing andarticulating the tones properly and accurately. These aspects are also related to a person’sability to do movements flexibly in line with the tempo and the rhythm of the song.Extramusical aspects are related to one’s desire, motivation, and passion to follow the processof acquiring singing ability and doing dance movements (choralography). As a matter of fact,some choirs currently focus on simply building and developing intramusical aspects; hence,they do not take into account the extramusical aspects. The current qualitative research aimsat exploring how extramusical aspects or non-technical aspects have an effect on the abilityof singing and doing dance movement (choralography) in the choir. The results of the researchdemonstrate that parts of extramusical aspects such as physical exercise, environmentalexploration, management of emotion, and mental building, take part in manipulating one’sability in singing and doing dance movements, particularly in a choir. Dalam paduan suara, terdapat dua aspek penting yang memiliki peran yang cukup besar dalammembentuk kemampuan bernyanyi dan gerak tari seseorang, yaitu aspek intramusikal danekstramusikal. Aspek intramusikal berkaitan dengan kemampuan seseorang dalammemproduksi dan membunyikan nada dengan baik dan benar, dan dengan kemampuanseseorang dalam melakukan gerakan dengan luwes dan lentur sesuai dengan tempo atau ritmelagu yang dibawakan. Aspek ekstramusikal berkaitan dengan keinginan, motivasi dan tekaddari seseorang untuk berproses hingga memperoleh kemampuan bernyanyi dan gerak tari(choralography). Permasalahannya, saat ini banyak paduan suara yang hanya berfokus padamembangun dan mengembangkan aspek intramusikal saja dan mengesampingkan aspekekstramusikal. Penelitian kualitatif ini bertujuan untuk menelaah pengaruh aspekekstramusikal terhadap kemampuan bernyanyi dan gerak tari (choralography) dalam paduansuara. Dari hasil penelitian ditemukan bahwa olah fisik, eksplorasi lingkungan, pemanfaatanemosi, dan pembentukan mental, yang merupakan bagian dari aspek ekstramusikal memilikipengaruh dalam membentuk kemampuan bernyanyi dan gerak tari seseorang, khususnyadalam paduan suara